DOES THE VILLAGE FUND MANAGEMENT HAS BEEN ACCOUNTABLE? (EMPIRICAL STUDY OF VILLAGE FUND MANAGEMENT IN WONOGIRI REGENCY, INDONESIA) - Elwas tantyo Pranowo; Mahameru Rosy Rocchmatulloh (Universitas Tidar, 2022)
Village fund management accountability is a form of a village government obligation to account for the performance of village financial management. The amount of village funds that are not small will lead to various frauds so that village supervision and accountability are needed for the community as trustees. So this research aims to examine leadership, village apparatus competence, community participation, and organizational commitment. The research population of all villages in Wonogiri Regency obtained a sample of 207 people, there is one data that is out of order due to heteroscedasticity problems. The results showed that leadership, competence, and organizational commitment had a positive and significant effect on village fund management accountability, while community participation had no effect on village fund management accountability.